TINJAUAN YURIDIS PEMANFAATAN RUANG BERDASARKAN PERATURAN GUBERNUR NOMOR 108 TAHUN 2008 - Salsabilla Reypianisha Mukhtar; Metty Soletri (Fakultas Hukum Universitas Trisakti, 2022)
The Governor Regulation Number 108 of 2008 is violated since there is insufficient oversight and control over how space is used. Problem formulation: How is the DKI Jakarta Governor Regulation No. 108 of 2008 implemented within the framework of Law Number 26 of 2007 pertaining to Spatial Planning Law, and how is the Incompatibility of Space Utilization by PT Betaconcrete Mixerindo (Betamix) used to carry out activities Concrete Batching Plant in Governor Regulation No. 108 of 2008 used to carry out activities? The research approach, judicial normative with the nature of descriptive analytical research, uses primary data, such as field research and respondent interviews, in addition to secondary data for literature analyses. Deductively inferred conclusions from qualitative analysis Deductive reasoning was used to qualitatively assess and draw conclusions. In order to maintain harmony and integration between the center and the regions, the research, discussion, and conclusion suggest that the Central Government delegate authority to the Provincial DPRD to create regional regulations. They also recommend applying the Lex Specialist Derogat Legi Generali Principle to prevent conflicts between general laws and special laws. According to current laws, PT Betaconcrete Mixerindo executes space utilization or Concrete Batching Plant activities without the necessary permits.